O impacto dos gastos com assistência estudantil na taxa de sucesso das universidades federais do Nordeste - Costa, Thaisa Machado Marques (2019)
The present research aimed to investigate the impact of student assistance expenditures on the success rate of Federal Universities in the Northeast region. The empirical analysis of the study applied the use of econometric techniques of panel data with the use of data between 14 Federal Universities of the Northeast region in the period between 2009 to 2017. Estimates were made through the stacked data models, fixed-effect model and model of random effect, besides tests to choose the most appropriate model. The results indicated a positive correlation between student assistance expenses and the success rate of the universities analyzed, corroborating with the literature that points to the importance of student assistance in reducing the number of students leaving educational institutions without completing their courses.